Indicadores físicos, químicos e biológicos da integridade ambiental em seis córregos da porção superior da bacia do rio Monjolinho, São Carlos-SP, Brasil - Barrilli, Germano Henrique Costa (Universidade Federal de São Carlos, 2014)
The analyses of the relative condition factor in fish community and of the benthic macroinvertebrates communities structure were used as a tool for assessing the influence of disturbances and water quality in the tropical streams of the upper portion of Monjolinho River basin, São Carlos, SP, Brazil. The condition factor revealed different responses of the fish species regarding the organic pollution effect. Astyanax cf paranae was found to be a sensitive species, Phalloceros harpagos to be tolerant, and Poecilia reticulate to be resistant. The analysis of the benthic macroinvertebrate community structure showed that these populations are affected by the loss of environmental quality, resulting in great differences in species diversity, with the absence of groups considered sensitive to pollution and dominance of resistant groups. In this portion of the Monjolinho River basin it was possible to identify streams with high environmental integrity as the Espraiado stream, up to strongly polluted streams as the Belvedere stream.
Keywords: Ecologia; Córregos; Impacto ambiental; Peixes de riachos; Fator de condição; Macroinvertebrados bentônicos; Tropical streams; Environmental impact; Stream fishes; Condition factor; Benthic macroinvertebrates; Water quality; CIENCIAS BIOLOGICAS::ECOLOGIA